Achieving Peace in Northern Mali Past Agreements, Local Conflicts, and the Prospects for a Durable Settlement - Pezard, Stephanie (RAND Corporation, 2015)
This report examines the prospects for stabilization in Mali following the political and military crisis that began in 2012. To this end, it examines Mali's peace settlements since the early 1990s to identify flaws and successes. The report also explores whether Mali's neighbor Niger owes its current stability to a more favorable context, shrewd policies, or sheer luck, and whether it might offer a model of resilience for Mali.